Arthroscopic approach and intra‐articular anatomy of the dorsal and plantar synovial compartments of the bovine tarsocrural joint. Issue 1 (January 2017) - Lardé, Hélène; Nichols, Sylvain; Babkine, Marie; Desrochers, André
Abstract: Objective: To determine arthroscopic approaches to the dorsal and plantar synovial compartments of the tarsocrural joint in adult cattle, and to describe the arthroscopic intra‐articular anatomy from each approach. Study Design: Ex vivo study. Animals: Fresh adult bovine cadavers ( n = 7). Methods: Two tarsocrural joint were injected with latex to determine arthroscopic portal locations and arthroscopy of the tarsocrural joint of 12 tarsi was performed. The dorsolateral approach was made through the large pouch located between the long digital extensor and peroneus longus tendons. The dorsomedial approach was made just medial to the common synovial sheath of the tibialis cranialis, peroneus tertius, and long digital extensor tendons. The plantarolateral and plantaromedial approaches were made lateral and medial to the tarsal tendon sheath, respectively. Results: Each approach allowed visualization of the distal tibia articulating with the proximal trochlea of the talus. Consistently observed structures included the distal intermediate ridge of the tibia, and the medial and lateral trochlear ridges and trochlear groove of the talus. Lateral and medial malleoli were best assessed from dorsal approaches. From the lateral approaches evaluation of the abaxial surface of the lateral trochlear ridge allowed visualization of the fibulocalcaneal joint. From the plantar approaches additional observed structures included the coracoid process of the calcaneus, plantar trochlea of the talus, and plantar talotibial and talofibular ligaments. Conclusion: In cattle, the dorsolateral and plantarolateral approaches allowed for the best evaluation of the dorsal and plantar aspects of the tarsocrural joint, respectively.